City councils of small and medium cities in Sverdlovskaya oblast: potential of autonomy in relations with the city head - Panov, P.V. (Perm Federal Research Centre Journal, 2019)
The realization of a city council political potential depends largely on how much autonomy is given to local legislature by the head of the municipality. If the head manages to promote a pool of “his own candidates” into a city council, the deputy corps is under control of the head, hence the political potential of the representative body of local government remains not fully realized. In the same time, there can be other influential actors in the local political field, first of all, business groups that seek to realize their influence through their presence in local legislature. Theoretically, that increases the autonomy and political weight of the representative body of local government. The study of the relationship between city councils and heads of small and medium-sized cities of Sverdlovskaya oblast leads to conclusion that autonomy of local legislature from the head of the city varies in nature and in sources in different social and economic environment, and it is determined by several sets of factors constellations. In singleindustry towns, the autonomy of city councils from the head of the city may be the result of the political activity of a city-forming enterprise, whereas in non-industrial cities it may result in fragmentation of local elite and activity of small and medium-sized businesses.